(3aGQW GdhGQO aj bUU GdTjN GdgGOi Edi WQjb GdYHGOs - (3eMeO aGVd GdJfOZjs ((3ehQJjGfjG s)
(3ChdgG (B:s
(3hHYO ajbhd CabQ GdNdb Edi ehdGg Cfg WdH ef HYV JdGejP gPG GdTjN hHYV Hfjg Cf CVY dge ecJhHkG ai CNHGQ gPG GdTjN aGeJKdK CeQge GeJKGdoG dbhdg Udi Gddg Ydjg hSde (B" (3GPcQhG eMGSf ehJGce (B" s
(3BNQgG (B:s
(3hbGd ajg eQjOg GdTjN GdeNJGQ Hf eMeO bUjOI hdeG Jhdi XgQI GdCfhGQ YfOg aUhJ GdWHd GdPi SeYg GdfGS KdGKI CjGe hGdQGFMI GdWjHI GdJi JTe YfOg hGdYjf GdJi JSjd Ydi GdbdjH ef LgI s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG TQhM hJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJGQjNs